Inconsistency of Seams on the Uterus after Cesara Section Problems and Ways of their Solution - Farida Mirzaevna Ayupova1, Nargiza Mirzaevna Umarova2, Gulnara Makhsudovna N (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cesarean section is currently the most common delivery surgery, which leads to the occurrence of diverse innature changes from the internal genital organs. This primarily concerns the uterus, where a postoperative scarforms in the area of the former incision. This article presents histomorphological and immunohistochemicalsigns of a uterine scar after cesarean section in the lower uterine segment. The features of tissue regenerationin the area of the incision made on the uterus after cesarean section were revealed. Some method fordiagnosing and treating uterine scar failure are also presented.